The all-American jump and jive jig - Proeller Hueston, Marie (Sterling Pub. Co., 2010)
All across the country children are jumping and jiving to their own unique dances, be it the Rockland Sock Hop from Maine, the Lubbock Line Dance from Texas, or the Hilo Hula from Hawaii.